Пристрій виявлення радіоакустичних закладних пристроїв - Коробка, С. В. (ХНУРЕ, 2023)
The focus of qualifying work is technical protection of acoustic information. The objective of qualifying work is design a scanning receiver for location of secret intelligence devices.In theoretical part of qualifying work the methods and technologies of information protection via scanning receivers were considered. In practical part of qualifying work were developed: the structural scheme of scanning receiver; circuit realization of the active Chebyshev band-pass filter, frequency mixers, intermediate-frequency amplifier and crystal oscillator. Numerical analysis methods of linear and nonlinear circuits and MathCAD software environment were used.
Keywords: радіоакустичний пристрій; кібербезпека